Muslim Parents’ Communication Approach to Adolescents according to Al-Tarbiyyah Al-Rashīdah by ‘Abd al-Karīm Bakkār - Safinah Ismail; Abur Hamdi Usman; Mariam Abd. Majid; Abdul Wahab Md. Ali; Rosmawati Mohamad Rasit; Zulkefli Aini; Siti Khaulah Mohd Hamzah Murghayah (Journal of Islamic Thought and Civilization, 2024)
The current study attempted to define and examine the concept of family in the Islamic context. Specifically, it addressed the issues and challenges related to parental communication in the modern day based on the strategies and suggestions proposed by ‘Abd al-Karīm Bakkār in his book Al-Tarbiyyah Al-Rashīdah (Successful Family Upbringing). This book is a guide to cultivating and nurturing a Muslim family in order to achieve the best outcomes through effective communication. The ultimate aim is to fortify the familial bonds. The current study used content analysis to examine and interpret the data extracted from the fourth volume of series entitled Al-Murāhiq (The Adolescents). This volume was the study’s main reference as it is set against the background of contemporary Muslim family issues along with suggested solutions by the author who identified certain strategies to enhance family ties and bonds. These strategies include kindness to relatives, effective interaction, listening, respecting, non-domination, and not pressurizing 5the children. Moreover, avoiding provocation of anger, paying attention to their problems as well as being polite to them are also among the strategies to enhance familial ties. The findings highlight the effectiveness of these strategies in bringing about positive parenting. Muslim parents therefore, can use ‘Abd al-Karīm Bakkār’s communication strategies to enhance their children’s moral, physical, mental, and spiritual development.